'Un dessein qui plait à la vue' (Bulletin KNOB, 1994)
In 1733-'36 the Prince of Orange had the 'Huis Ten Bosch' (House Ten Bosch) near The Hague modernized and extended with two wings. The design for this was made by Daniel Marot and the architectural management of its execution was performed by Anthonie Coulon. Some documents which had been unknown so far, have revealed a controversy taking place during construction in 1734 between the designer Marot, the works foreman Coulon and the representative of the Prince, councillor Duncan. The chiefly oral contact between the commissioner and his architect seems to have been an important cause of the problems.A contact, which in the presence of the Prince worked excellently for the designing architect, who continued to be involved in the project, as well as for the executing architect. However, in the commissioner's absence this immediately led to great problems. This also makes clear how in a large building project all those involved had to be present regularly, since only the broad lines had been laid down according to specifications and a lot of elements still had to be designed, discussed and executed during construction. Thus the elaborate complaint made by Coulon to the Prince of Orange on the way in which the latter's representative Duncan had treated him, provides an unusually detailed insight into the architects' and building practice during the first half of the I5th century.In that period, distinguished architecture was dominated by those who had the knack of ornamentation, such as Marot, the plasterer Van Logteren and the sculptor Van Baurscheit jr: decorators who had not come directly from the building profession, but from the world of the ornament. The master carpenter who had worked his way up in the building profession was only allotted the role of works foreman at most in the upper circles of the Dutch world of building. Coulon's document indicates the controversy that could arise when such an architect from the building profession was no longer satisfied with his tacit role, but wished to put his experience into active practice in order to correct all kinds of technical and practical imperfections in a fine design made by illustrious hands.